When Domains Spill Over: The Relationships of Work-Family Conflict With Indian Police Affective and Continuance Commitment - Qureshi, Hanif (International journal of offender therapy and comparative criminology, 2019)
Policing is a stressful occupation that may give rise to work-family conflict (WFC). WFC arises when the work domain encroaches into the family domain, or vice versa, causing officers to become less attached to their job and the police organization. Using survey data collected from a sample of police officers in India, we examined the relationship between four dimensions of WFC (time-based, strain-based, behavior-based, and family-based WFC) and two dimensions of organizational commitment (continuance and affective). Family-based WFC was found to reduce continuance commitment, while strain-based WFC reduced affective commitment. Time-based, strain-based, and behavior-based WFC increased continuance commitment. We examined the implications of these findings for police policy makers and administrators. In addition, we also discussed our findings in the context of cross-cultural comparisons.